2022
DOI: 10.1016/j.idcr.2022.e01439
|View full text |Cite
|
Sign up to set email alerts
|

Immune thrombocytopenic purpura and legionella infection: A case report highlighting the association

Abstract: Immune thrombocytopenic purpura (ITP) can be acquired or secondary to other drugs, infections, or autoimmune disorders. Legionella is a known intracellular organism that causes Legionnaire's disease and affects the lungs. Presented is the first case showing a direct association between Legionella and ITP. Our patient was a 61-year-old female with a past medical history of asthma whose clinical presentation was consistent with pneumonia secondary to Legi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The first case was reported in 1982 by Riggs et al [ 122 ]. Recently, Javed et al reported a case of a 61-year-old woman with critical bleeding and severe thrombocytopenia [ 123 ].…”
Section: Bacteriemiamentioning
confidence: 99%
“…The first case was reported in 1982 by Riggs et al [ 122 ]. Recently, Javed et al reported a case of a 61-year-old woman with critical bleeding and severe thrombocytopenia [ 123 ].…”
Section: Bacteriemiamentioning
confidence: 99%